DAMPAK MEDIA SOCIAL TERHADAP CARA POLA PIKIR ANAK MUDA GENERASI Z DALAM KETIMPANGAN PEMIKIRAN LGBTDI DKI JAKARTA - Juniawan Mandala Putra; Erlina Puspitaloka Mahadewi (CV. ADIBA AISHA AMIRA, 2024)
Another thing is that the delivery of information is no longer from media A or media B, but social media, which is currently growing among the public, making information barriers no longer hanky, which means that within seconds the information conveyed will be received immediately without waiting for news on TV. or the national media reports, therefore a social media is not only limited to showing one's sociality but can deliver news in a few seconds to the public's proper rights. This phenomenon occurs because access to information is unlimited and no longer sees age restrictions to be able to access these media such as Twitter, Facebook, Instagram, line, tiktok are no longer obstacles for someone to download and open access to find the information he needs or without it. realizing that the information appears automatically makes someone curious and wants to know more about it. The method in this study was a literature review of the Library with a descriptive approach and field surveys that took a sample of 68 male LGBT respondents in the DKI Jakarta area. From the survey data above, it produces a surprising conclusion, namely the generation that is currently growing and developing is a generation that is not blind to technology but sensitive to technology compared to previous generations where all aspects that were previously closed and taboo at the present time have become hallmarks of technology. umrah among generation Z, the fear of researchers when they are caught and talk to them is that LGBT treatment has entered junior and senior high school students, where this generation is the next generation, and the prevalence of male sexually transmitted diseases in society is very high, ranging in 1 year in 2021 in DKI Jakarta 20,583 people.